Temporal variations in the food habits of some fish species in Lake Nokoué, Benin - GNOHOSSOU, Pierre; LALEYE, PHILIPPE A. (My University, 2013)
Stomach contents of the 12 most abundant fish species in Lake Nokoué, Benin, collected between 2003 and 2005, were analysed for temporal variations in their diet. Several species showed seasonal shifts in their diets based on benthic prey abundance and biomass variation, which are influenced by physico-chemical environmental changes. Five trophic guilds were identified: detritivorous, microbenthivorous, macrobenthivorous, zooplanktivorous and piscivorous. Trophic guilds in 2003–2005, compared to 1961, showed a decrease of benthivorous species, which illustrates the vulnerability of this group whose prey are particularly exposed to organic pollution.
Keywords: fish diet; lagoon; spatiotemporal variation; trophic guilds.